Before I was CEO life stories and lessons from leaders before they reached the top - Vanham, Peter 1986- (Wiley, 2017)
"Have you always known what you wanted to be in life? What are some & ldquo;watershed moments & rdquo; that made you who you are? When did you get on track to become a successful CEO? It started with three questions at Davos. The younger Peter Vanham looked to the answers from the elite leaders he asked to validate his own career choice, and the rich, private wisdom he received revealed more about building a career than he & rsquo;d found anywhere else. He shares it all with you in Before I Was CEO. For everyone who lays awake at night wondering if they & rsquo;re heading up or down the corporate ladder, this collection of personal stories from a remarkable group of the most accomplished men and women in business today proves everyone can put themselves in the C-suite by taking a variety of different paths & mdash;it & rsquo;s all how you do it. Some found opportunity through adversity and others came by their big-break moments through serendipity. A group of them walked away from corporate life and lived in other ways and all of them made calculated moves to advance their careers. In their own words, read how it all unfolded, the tough decisions they wrestled, the risks and rewards they saw, and how it all came together. You don & rsquo;t need a royal pedigree or Ivy League education to reach the top as long as you: & bull; Value family, leave home, and make informed decisions based on your dreams & bull; Take the first thirty-five years of your life to discover what you & rsquo;re interested in and don & rsquo;t rush to be a CEO & nbsp; & bull; Strategically deal with failure, remember the lessons you learned, and adapt to situations you can & rsquo;t change You aren & rsquo;t the first person to be at the crossroads you & rsquo;re standing in, and with the motivating and instructive stories in Before I Was CEO, you may be answering a young journalist & rsquo;s questions at Davos one day"--
Includes bibliographical references and index. - Print version record
Keywords: Executives; Leadership; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior